Early childhood sleep quality in a pediatric cohort: sex-specific differences - Bose, Sonali; Ross, Kristie R.; Zheng, Xin; Xhani, Naim; Ötvös, Tamás; Merced-Nieves, Francheska M.; Redline, Susan; Wright, Rosalind J. (Frontiers in Sleep, 2025)
BackgroundPoor sleep health in childhood has significant implications for life-long physical, cognitive, and behavioral outcomes, but sleep problems and potential developmentally-driven sex differences in early childhood are poorly understood.ObjectiveTo objectively assess sleep health and investigate sex-specific differences in sleep in early childhood.MethodsThree hundred thirty-six children enrolled in the PRogramming of Intergenerational Stress Mechanisms (PRISM) pregnancy cohort in Boston and New York City underwent actigraphy for 7 days. A subset (n = 117) completed home unattended Type II polysomnography (PSG). Sleep parameters from actigraphy and PSG were examined using standard descriptive analyses, and non-parametric tests of comparison of means, specifically two-sample Wilcoxon Rank Sum tests, were used to assess differences between boys and girls.ResultsChildren were median (IQR) age of 6.9 (4.9, 8.9) years, half were male, and most were Black (46.2%) and/or Hispanic (33.9%). On actigraphy, average sleep duration and sleep efficiency were low compared to published normative data, with median (IQR) time spent asleep of 7.8 (7.4, 8.3) hours and sleep efficiency of 79.1% (74.7, 82.6). Wake duration after sleep onset (WASO) assessed by actigraphy was elevated (median (IQR) of 1.8 (1.4, 2.2) hours), and significantly worse among boys compared to girls (p = 0.0007). Overall, boys had significantly more restless and fragmented sleep as measured by both actigraphy and PSG. Sleep disordered breathing events were infrequent, with median (IQR) Apnea-Hypopnea Index of 0.7 (0.3, 1.3) events per hour.ConclusionClinically significant and objectively assessed sleep disturbance was common in this pediatric cohort, and worse in boys compared to girls. These findings emphasize early sex-based sleep disparities warranting intervention to intercept lifelong consequences of poor sleep in early childhood.